Quality and quantity revisited - Piovani, Juan Ignacio; Beigel, Fernanda (2015)
Este trabajo se propone discutir el enfoque metodológico cualitativo de Jack Katz en su marco histórico de producción. De este modo, se pretende analizar la relevancia actual de estos debates y su impacto en la problematización de la dualidad "cualitativo-cuantitativo". Revisitar las ideas de Katz y complementarlas con algunos comentarios críticos sobre los límites, usos indebidos y los sesgos de las cuatro erres (representatividad, reactividad, fiabilidad y reproducibilidad) en la investigación cuantitativa supone una importante contribución a la comprensión del valor de la investigación cualitativa en sus propios términos. En muchos sentidos, las ideas metodológicas de Katz anticiparon desarrollos posteriores.
This paper attempts to discuss the qualitative methodological approach of Jack Katz in its historical framework of production. In doing so, we aim to analyze the actual relevance of these discussions and their impact in the qualitative-quantitative dilemma. Revisiting Katz's ideas and complementing them with some critical remarks about the limits, misuses and biases of the four R's (representativeness, reactivity, reliability and replicability) in quantitative research implies a significant contribution to the understanding of qualitative research's value in its own terms. In many ways, Katz's methodological ideas anticipated later developments.
Keywords: Investigación cualitativa; Jack Katz; Representatividad; Reactividad; Fiabilidad; Reproducibilidad; Qualitative research; Jack Katz; Representativeness; Reactivity; Reliability; Replicability